Empowering Women Farmers through STIBs: Insights from Multi-stakeholder Dialogues in Makaltala and Balarampur Learning Labs, West Bengal, India - CGIAR Gender Equality Initiative (CGIAR Initiative on Gender Equality, 2024)
On February 8th and 12th, the CGIAR Initiative on Gender Equality, HER+ Work Package EMPOWER, led by IRRI, organized two inception dialogues in Makaltala and Balarampur villages of the North and South 24 Parganas districts of West Bengal, respectively. These villages are the pilot learning lab sites for the implementation of Socio-Technical Innovation Bundles (STIBs), co-designed with local stakeholders and women farmers. The dialogues provided an opportunity to the participating women farmers to get acquainted with the partners implementing different social and technical innovations. These dialogues were designed with two objectives: to familiarize the farmers with the planned interventions and of what to anticipate in the coming months, and to have the women farmers articulate their perceived role in this process as well as the challenges they face or might face moving forward.